2004
DOI: 10.1074/jbc.m401321200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Transcription Regulatory Complex Containing Death Domain-associated Protein and the ATR-X Syndrome Protein

Abstract: Death domain-associated protein (Daxx) is a multifunctional protein that modulates both apoptosis and transcription. Within the nucleus, Daxx is a component of the promyelocytic leukemia protein (PML) nuclear bodies (NBs) and interacts with a number of transcription factors, yet its precise role in transcription remains elusive. To further define the function of Daxx, we have isolated its interacting proteins in the nucleus using epitope-tagged affinity purification and identified X-linked mental retardation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
186
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(204 citation statements)
references
References 33 publications
15
186
3
Order By: Relevance
“…In addition, Daxx forms a complex with protein ATRX and this complex displays chromatin-remodeling activity (Xue et al, 2003;Ishov et al, 2004;Tang et al, 2004). Besides chromatin remodeling, ATRX also possesses DNA methylation activity (Gibbons et al, 2000); DNA methylation is generally associated with repression of transcription (reviewed in Baylin and Ohm, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Daxx forms a complex with protein ATRX and this complex displays chromatin-remodeling activity (Xue et al, 2003;Ishov et al, 2004;Tang et al, 2004). Besides chromatin remodeling, ATRX also possesses DNA methylation activity (Gibbons et al, 2000); DNA methylation is generally associated with repression of transcription (reviewed in Baylin and Ohm, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Baculovirus expressed ATRX protein containing engineered patient mutations within the SNF2 domain were shown to have attenuated ATPase activity compared to the wild-type (WT) protein. 15 Similarly, expression of the PHD domain in bacteria demonstrated that patient mutations impaired DNA-binding activity. 18 Collectively, these studies suggest that some mutations may interfere directly with function while others may have an indirect effect through altered protein stability or aberrant subnuclear targeting of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…11 -14 The ATRX protein also localizes to PML-NBs where it interacts with Daxx, a transcriptional and apoptotic regulator. 12,15,16 ATRX is also involved in the regulation of methylation at ribosomal DNA (rDNA) repeats. 17 Given that ATRX acts at multiple locations within the nucleus, some mutations are likely to alter subnuclear localization thereby reducing function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its interactions with MeCP2 and HP1, ATRX has also been shown to directly interact with the death-associated domain protein Daxx (Xue et al, 2003;Tang et al, 2004), which is known to have an important role in apoptotic signaling in a variety of cell types, including neurons (Raoul et al, 2002;Junn et al, 2005). ATRX and Daxx are known to co-localize to pericentromeric heterochromatin and at promyelocytic leukemia bodies in vivo (Xue et al, 2003), and ATRX/Daxx complex associations have been demonstrated to exhibit ATPase-dependent mononucleosomal remodeling activity (Tang et al, 2004). Nucleosomal dynamics, specifically histone deposition and eviction, are tightly regulated by the actions of specific chaperone proteins and via the enzymatic activity of ATPdependent remodelers.…”
Section: Atrx: a Critical Regulator Of Chromatin State And Histone Dymentioning
confidence: 99%